The Penderwicks at Point Mouette - Birdsall, Jeanne (Yearling, 2012)
Rosalind heads to the beach when summer arrives, and the rest of the Penderwick girls go to a cozy cottage in Maine with Aunt Claire, leaving Skye feeling slightly overwhelmed with her new role as the oldest available Penderwick.